P Pentingnya Berbahasa Lisan pada Peserta Didik Sekolah Dasar di SDN Neglasari - Rakhman, Patra Aghtiar; Rokmanah, Siti; Yuliana, Yuliana (Educational Consultant & Counseling Career (EC3) Mataram, 2023)
Tobe be able to find out problems related to Indonesian language as well as alternative solutions in learning in class II at SDN Neglasar. The method used in this research uses qualitative research in the realm of case study research and literature study. The researcher in the realm of case study research to related to spoken language and the existence of solutions in the school. The result of the research show that spoken language can help students understand a meaning using a series of picture media, using alternative solutions to the problem of not understanding spoken language using media in the form of a series of picture media which is used optimally to develop and provide ecplanations for children’s oral language skills. Through a series to train children’s language development. By observing he picture, children will then get a story idea from the picture